Coated graphite as well as preparation method and application of coated graphite

By forming a continuous cladding layer of fast ion conductors on the graphite surface, the problem of insufficient fast charging performance in the prior art is solved, and the fast charging performance is significantly improved, which is suitable for applications in the field of lithium-ion batteries.

CN119447292APending Publication Date: 2025-02-14HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310940965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The fast ion conductor-covered graphite composite materials produced in the prior art cannot meet the requirements of higher fast charging performance, affecting their application in the field of lithium-ion batteries.

Method used

By forming a continuous cladding layer of fast ion conductor on the graphite surface, the average particle size of the fast ion conductor is controlled at <5 nm, with a mass ratio of (0.3-0.5): 100, using titanium oxide, lithium titanate, zirconium oxide, alumina and Materials such as lithium aluminate are used as fast ion conductors, and polymer polymers, fatty acids, fatty amines and organic phosphine compounds are added as ligands during the preparation process.

Benefits of technology

The rapid charging performance is achieved significantly improved. The fast ion conductor is evenly distributed on the graphite surface, avoiding island-like cladding, ensuring continuous coverage of active sites, and thus improving the fast charging performance of coated graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447292A_ABST
    Figure CN119447292A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery material preparation, and particularly relates to coated graphite as well as a preparation method and application of the coated graphite. The coated graphite comprises graphite and a fast ion conductor continuous coating layer coated on the surface of the graphite, the average particle size of a fast ion conductor in the coated graphite is less than 5nm, the average particle size of the fast ion conductor is small, the fast ion conductor presents a continuous coating effect, and an independent island-shaped coating effect does not appear. It is guaranteed that active sites of the fast ion conductor continuously cover the surface of the graphite, the active sites are increased, and the fast charging performance of the coated graphite is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and in particular relates to coated graphite and a preparation method and application of the coated graphite. Background Art

[0002] Market demands for fast-charging performance in lithium-ion batteries continue to increase. Currently, one approach to improving the fast-charging performance of negative electrode materials is to modify the material's surface to enhance its ion mobility and increase its ionic and electronic conductivity. Fast-ion conductors are compounds with high lithium-ion conductivity that enable rapid lithium-ion exchange during the charge and discharge process, effectively improving fast-charging performance.

[0003] Coating a fast ion conductor on the graphite surface can improve the fast charging performance of the graphite material to a certain extent. However, the fast ion conductor-coated graphite composite materials obtained by the existing technology cannot meet the requirements of higher fast charging performance, which affects the application of the fast ion conductor-coated graphite composite materials in the field of lithium-ion batteries. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a coated graphite with good fast charging performance and a preparation method and application of the coated graphite.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a coated graphite, characterized in that it comprises graphite and a continuous coating layer of a fast ion conductor coated on the surface of the graphite;

[0007] The average particle size of the fast ion conductor in the fast ion conductor continuous coating layer is less than 5 nm.

[0008] The mass ratio of the fast ion conductor to the graphite in the coated graphite is (0.3-0.5):100.

[0009] The fast ion conductor in the fast ion conductor continuous coating layer includes at least one of titanium oxide, lithium titanate, zirconium oxide, aluminum oxide and lithium metaaluminate.

[0010] The raw materials for the coated graphite include graphite, a fast ion conductor precursor and a ligand; wherein the fast ion conductor precursor is at least one of a titanium-containing compound, an aluminum-containing compound and a zirconium-containing compound;

[0011] When the fast ion conductor is lithium titanate and / or lithium metaaluminate, the raw material for coating the graphite further includes a lithium-containing compound.

[0012] Preferably, the ligand is at least one of a high molecular weight polymer, a fatty acid, a fatty amine and an organic phosphine compound.

[0013] The molar ratio of the ligand to the fast ion conductor precursor is (2-3):1;

[0014] Preferably, the high molecular weight polymer is at least one of polyvinyl pyrrolidone and polyacrylic acid;

[0015] Preferably, the fatty acid is at least one of stearic acid and oleic acid;

[0016] Preferably, the fatty amine is at least one of dodecylamine, hexadecylamine, octadecylamine and oleylamine;

[0017] Preferably, the organic phosphine compound is at least one of trioctylphosphine and trioctylphosphine oxide.

[0018] The graphite is artificial graphite, which is not specifically limited. Its particle size can be any value between 1 and 50 μm, such as 10 μm, 20 μm, 40 μm, etc.

[0019] The raw material of the coated graphite also includes a solvent;

[0020] Preferably, the solvent is an organic solvent;

[0021] Preferably, the solvent is ethanol.

[0022] The coated graphite provided by the present invention includes graphite and a continuous coating layer of a fast ion conductor coated on the surface of the graphite. The average particle size of the fast ion conductor in the coated graphite is less than 5nm, the average particle size of the fast ion conductor is small, the fast ion conductor presents a continuous coating effect, and no separate island coating effect occurs, thereby ensuring that the active sites of the fast ion conductor are continuously covered on the graphite surface, increasing the active sites, and improving the fast charging performance of the coated graphite.

[0023] The present invention controls the average particle size of the fast ion conductor in the coated graphite to be less than 5nm. The smaller the active site, the more obvious island coating can be avoided, and the fast ion conductor can be more evenly distributed on the graphite surface. When the particle size of the fast ion conductor exceeds 5nm, islands and uneven coating will occur.

[0024] The present invention also provides a method for preparing coated graphite, comprising: mixing various raw materials, kneading, and heat treating;

[0025] The raw materials include graphite, fast ion conductor precursors and ligands.

[0026] The ligand is at least one of a high molecular weight polymer, a fatty acid, a fatty amine and an organic phosphine compound;

[0027] Preferably, the high molecular weight polymer is at least one of polyvinyl pyrrolidone and polyacrylic acid;

[0028] Preferably, the fatty acid is at least one of stearic acid and oleic acid;

[0029] Preferably, the fatty amine is at least one of dodecylamine, hexadecylamine, octadecylamine and oleylamine;

[0030] Preferably, the organic phosphine compound is at least one of trioctylphosphine and trioctylphosphine oxide.

[0031] The molar ratio of the ligand to the fast ion conductor precursor is (2-3):1;

[0032] Preferably, the fast ion conductor precursor is at least one of a titanium-containing compound, an aluminum-containing compound, and a zirconium-containing compound.

[0033] The raw materials for coating graphite also include solvents;

[0034] Preferably, the solvent is an organic solvent;

[0035] Preferably, the solvent is ethanol.

[0036] The kneading is carried out at room temperature;

[0037] Preferably, the kneading time is 8-12h;

[0038] Preferably, the heat treatment temperature is 400-950°C and the time is 2-3h;

[0039] Preferably, during the heat treatment, the heating rate is 1-10°C / min.

[0040] The preparation method of coated graphite provided by the present invention uses at least one of a high molecular weight polymer, a fatty acid, a fatty amine and an organic phosphine compound as a ligand, which is used as the raw material for coating the graphite. This can assist the active sites of the fast ion conductor to be continuously covered on the graphite surface, improve the nucleation process of the active sites of the fast ion conductor, inhibit the individual generation of island-shaped fast ion conductors, reduce the average particle size of the fast ion conductor to less than 5nm, and significantly improve the fast charging performance of the coated graphite.

[0041] The present invention also provides a negative electrode material comprising the above-mentioned coated graphite.

[0042] Furthermore, the present invention provides a battery comprising the above-mentioned negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0044] Figure 1 1 is the SEM spectrum of the coated graphite provided in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.

[0047] Example 1

[0048] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0049] This embodiment also provides a method for preparing coated graphite: 67.5 g of octadecylamine and 42.6 g of tetrabutyl titanate are dissolved in ethanol, stirred thoroughly for 1 hour using an electric stirrer, and then 2 kg of artificial graphite is added and stirred thoroughly for 1 hour. The mixed material is then placed in a kneading pot and kneaded at room temperature, with 200 ml of anhydrous ethanol added every 2 hours for a kneading time of 8 hours.

[0050] The kneaded material was placed in a carbonization furnace, nitrogen was introduced, and the temperature was raised to 400°C at a rate of 5°C / min and heat-treated for 3 hours to obtain TiO2-coated graphite.

[0051] Example 2

[0052] This embodiment provides a coated graphite, including graphite and a continuous coating layer of lithium titanate coated on the surface of the graphite, wherein the average particle size of the lithium titanate in the coating layer is less than 5 nm; and the mass ratio of lithium titanate to graphite in the coated graphite is 0.5:100.

[0053] This embodiment also provides a method for preparing coated graphite, comprising the following steps:

[0054] Dissolve 52.6 g of hexadecylamine, 37.1 g of tetrabutyl titanate (fast ion conductor precursor), and 5.75 g of lithium acetate in ethanol, stir thoroughly with an electric stirrer for 1 hour, then add 2 kg of artificial graphite and stir thoroughly for 1 hour, then put the mixed material into a kneading pot and knead at room temperature, adding 200 ml of anhydrous ethanol every 2 hours, and the kneading time is 10 hours.

[0055] The kneaded material was placed in a carbonization furnace, nitrogen was introduced, and the temperature was raised to 750° C. at a rate of 5° C. / min for heat treatment for 3 h to obtain lithium titanate-coated graphite.

[0056] Example 3

[0057] This embodiment provides a coated graphite, including graphite and a continuous coating layer of aluminum oxide coated on the surface of the graphite, wherein the average particle size of the aluminum oxide in the coating layer is less than 5 nm; and the mass ratio of aluminum oxide to graphite in the coated graphite is 0.5:100.

[0058] This embodiment also provides a method for preparing coated graphite, comprising the following steps:

[0059] Dissolve 72.7 g of dodecylamine and 40 g of aluminum isopropoxide in ethanol, stir thoroughly for 1 hour using an electric stirrer, then add 2 kg of artificial graphite and stir thoroughly for 1 hour, then put the mixed material into a kneading pot and knead at room temperature, adding 200 ml of anhydrous ethanol every 2 hours, and the kneading time is 12 hours.

[0060] The kneaded material was placed in a carbonization furnace, nitrogen was introduced, and the temperature was raised to 600°C at a rate of 5°C / min and heat-treated for 3 hours to obtain alumina-coated graphite.

[0061] Example 4

[0062] This embodiment provides a coated graphite, including graphite and a continuous coating layer of lithium aluminate coated on the surface of the graphite, wherein the average particle size of the lithium aluminate in the coating layer is less than 5 nm; and the mass ratio of lithium aluminate to graphite in the coated graphite is 0.5:100.

[0063] This embodiment also provides a method for preparing coated graphite, comprising the following steps:

[0064] Dissolve 81.2 g of oleylamine, 31 g of aluminum isopropoxide (fast ion conductor precursor), and 11.2 g of lithium carbonate in ethanol, stir thoroughly for 1 hour using an electric stirrer, then add 2 kg of artificial graphite and stir thoroughly for 1 hour, then put the mixed material into a kneading pot and knead at room temperature, adding 200 ml of anhydrous ethanol every 2 hours, and the kneading time is 10 hours.

[0065] The kneaded material was placed in a carbonization furnace, nitrogen was introduced, and the temperature was raised to 850° C. at a rate of 5° C. / min for heat treatment for 3 h to obtain lithium aluminate-coated graphite.

[0066] Example 5

[0067] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0068] This embodiment also provides a method for preparing coated graphite, which differs from Example 1 in that the molar ratio of octadecylamine to tetrabutyl titanate is 3:1.

[0069] Example 6

[0070] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0071] This embodiment provides a method for preparing coated graphite, which differs from Example 1 in that polyacrylic acid replaces octadecylamine, and the molar amounts of polyacrylic acid and octadecylamine are the same.

[0072] Example 7

[0073] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0074] This embodiment provides a method for preparing coated graphite, which differs from Example 1 in that stearic acid replaces octadecylamine, and the molar amounts of stearic acid and octadecylamine are the same.

[0075] Example 8

[0076] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0077] This embodiment provides a method for preparing coated graphite, which differs from Example 1 in that trioctylphosphine replaces octadecylamine, and the molar amounts of trioctylphosphine and octadecylamine are the same.

[0078] Example 9

[0079] This embodiment provides a coated graphite, including graphite and a continuous TiO2 coating layer coated on the surface of the graphite, wherein the average particle size of the TiO2 in the coating layer is less than 5 nm; the mass ratio of the fast ion conductor to the graphite in the coated graphite is 0.3:100.

[0080] This embodiment also provides a method for preparing coated graphite: 60.5 g of octadecylamine and 25.6 g of tetrabutyl titanate are dissolved in ethanol, stirred thoroughly for 1 hour using an electric stirrer, and then 2 kg of artificial graphite is added and stirred thoroughly for 1 hour. The mixed material is then placed in a kneading pot and kneaded at room temperature, with 200 ml of anhydrous ethanol added every 2 hours for a kneading time of 8 hours.

[0081] The kneaded material was placed in a carbonization furnace, nitrogen was introduced, and the temperature was raised to 400°C at a rate of 5°C / min and heat-treated for 3 hours to obtain TiO2-coated graphite.

[0082] Comparative Example 1

[0083] This comparative example provides a coated graphite, including graphite and a TiO2 coating layer coated on the surface of the graphite, the TiO2 coating layer is island-shaped and discontinuous, and the average particle size of TiO2 in the coating layer is 20-70nm; the mass ratio of TiO2 to graphite in the coated graphite is 0.5:100.

[0084] This comparative example also provides a method for preparing coated graphite: the difference from Example 1 is that octadecylamine is not added, and the remaining raw materials and their amounts are the same as those in Example 1.

[0085] Comparative Example 2

[0086] This comparative example provides a coated graphite, comprising graphite and a lithium titanate coating layer coated on the surface of the graphite, wherein the lithium titanate coating layer is island-shaped and discontinuous, and the average particle size of the lithium titanate in the coating layer is 20-70 nm; the mass ratio of lithium titanate to graphite in the coated graphite is 0.5:100.

[0087] This comparative example also provides a method for preparing coated graphite: the difference from Example 2 is that hexadecylamine is not added, and the remaining raw materials and their amounts are the same as those in Example 2.

[0088] Comparative Example 3

[0089] This comparative example provides a coated graphite, comprising graphite and an alumina coating layer coated on the surface of the graphite, wherein the alumina coating layer is island-shaped and discontinuous, and the average particle size of the alumina in the coating layer is 20-70 nm; the mass ratio of alumina to graphite in the coated graphite is 0.5:100.

[0090] This comparative example also provides a method for preparing coated graphite: the difference from Example 3 is that no dodecylamine is added, and the remaining raw materials and their amounts are the same as those in Example 3.

[0091] Comparative Example 4

[0092] This comparative example provides a coated graphite, comprising graphite and a lithium aluminate coating layer coated on the surface of the graphite, wherein the lithium aluminate coating layer is island-shaped and discontinuous, and the average particle size of the lithium aluminate in the coating layer is 20-70 nm; the mass ratio of lithium aluminate to graphite in the coated graphite is 0.5:100.

[0093] This comparative example also provides a method for preparing coated graphite: the difference from Example 4 is that oleylamine is not added, and the remaining raw materials and their amounts are the same as those in Example 4.

[0094] Comparative Example 5

[0095] This comparative example provides a method for preparing coated graphite, which differs from Example 1 in that the molar ratio of octadecylamine to tetrabutyl titanate is 1:1.

[0096] Comparative Example 6

[0097] This comparative example provides a method for preparing coated graphite, which differs from Example 1 in that the molar ratio of octadecylamine to tetrabutyl titanate is 4:1.

[0098] Test example

[0099] This test example provides the performance test results of the coated graphite of the embodiment and the comparative example, specifically including:

[0100] (1) Figure 1 is the SEM spectrum of the coated graphite provided in Example 1 and Comparative Example 1, Figure 1 The left picture in the middle is the graphite coated in comparative example 1, and the right picture is the graphite coated in embodiment 1. Figure 1 It can be seen that the particle size of TiO2 particles in the coated graphite in Comparative Example 1 is greater than 20nm, and separate islands appear, which is a discontinuous coating layer. The particle size of TiO2 particles in the coated graphite in Example 1 is less than 5nm, and no islands appear, which is a continuous coating layer.

[0101] (2) Button battery preparation method: the above-mentioned electrode materials are homogenized, and the active material (coated graphite provided in each embodiment and comparative example), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), conductive carbon black are mixed evenly in a ratio of 94.5:1.5:2.5:1.5 and a certain amount of deionized water; the evenly mixed slurry is scraped on the copper foil, and then placed in an 80°C oven for baking for 2 hours. After baking, it is rolled and punched to prepare a pole piece with a diameter of 12 mm, and finally assembled into a button battery according to the requirements.

[0102] Battery Performance Testing: The assembled batteries were placed in a constant temperature environment for 6 hours. Then, a BlueDian system was used to perform charge and discharge tests at different rates, with the battery charge and discharge voltage range of 0.005V-2V. The results are shown in the table below.

[0103] Table 1 Performance test results of coated graphite and batteries obtained in various embodiments and comparative examples

[0104]

[0105] By comparing Examples 1-4 and Comparative Examples 1-4, it can be seen that when graphite coated with a continuous coating layer of a fast ion conductor and a fast ion conductor particle size of less than 5 nm is used as the negative electrode active material, the rate performance of the lithium ion battery is significantly improved. From the above results, it can be seen that the addition of a ligand can effectively improve the nucleation process of the active site, thereby effectively improving the morphology of the coating, and significantly improving the particle size of the active site, which is basically less than 5 nm. By comparing Example 1, Example 5 and Comparative Examples 5-6, it can be seen that a ligand ratio and an active site ratio of 2-3:1 are more appropriate. A ligand ratio that is too low will affect the active site particle size and nucleation morphology. A ligand ratio that is too high will easily lead to excess ligand forming a complex with the active site, thereby affecting the performance of the negative electrode material.

[0106] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A coated graphite, characterized in that: It includes graphite and a fast ion conductor continuous coating layer coated on the surface of the graphite; The average particle size of the fast ion conductor in the fast ion conductor continuous coating layer is less than 5 nm.

2. The coated graphite according to claim 1, characterized in that The mass ratio of the fast ion conductor to the graphite in the coated graphite is (0.3-0.5):

100.

3. The coated graphite according to claim 1 or 2, characterized in that: The fast ion conductor in the fast ion conductor continuous coating layer includes at least one of titanium oxide, lithium titanate, zirconium oxide, aluminum oxide and lithium aluminate.

4. A method for preparing coated graphite, characterized in that: The raw materials include graphite, fast ion conductor precursor and ligand; the raw materials are mixed and then kneaded and heat treated.

5. The preparation method according to claim 4, characterized in that: The ligand is at least one of a high molecular weight polymer, a fatty acid, a fatty amine and an organic phosphine compound; Preferably, the high molecular polymer is at least one of polyvinyl pyrrolidone and polyacrylic acid; Preferably, the fatty acid is at least one of stearic acid and oleic acid; Preferably, the fatty amine is at least one of dodecylamine, hexadecylamine, octadecylamine and oleylamine; Preferably, the organic phosphine compound is at least one of trioctylphosphine and trioctylphosphine oxide.

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the ligand to the fast ion conductor precursor is (2-3):1; Preferably, the fast ion conductor precursor is at least one of a titanium-containing compound, an aluminum-containing compound and a zirconium-containing compound.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Its raw materials also include solvents; Preferably, the solvent is an organic solvent; Preferably, the solvent is ethanol.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The kneading is carried out at room temperature; Preferably, the kneading time is 8-12h; Preferably, the heat treatment temperature is 400-950°C and the time is 2-3h; Preferably, during the heat treatment, the heating rate is 1-10°C / min.

9. A negative electrode material, characterized in that: The invention comprises the coated graphite according to any one of claims 1 to 3 or the coated graphite prepared by the preparation method according to any one of claims 4 to 8.

10. A battery, characterized in that: Comprising the negative electrode material according to claim 9.